Service Culture Chain: Increasing Public Satisfaction - Aldri Frinaldi; Muhamad Ali Embi; Aziza Bila (Iapa Proceedings Conference, 2019)
Job Satisfaction is a cognitive assessment of an employee's effective evaluation of work. Employee satisfaction at work must be the main thing to be realized before satisfaction service is provide to customer. Employee who have good satisfaction at work will give a good performance, because job satisfaction is results of assessmet of employee performance toward job quality. Employee are inseparable from work culture of organization. Therefore, to improve value and image of organization, a service culture is needed to increase work satisfaction. This research uses quantitative methods with survey strategy. Determination of respondent using total sampling techniques. While data were collected using a questionnaire instrument that was valid and reliable. The collected data was processed used IBM SPSS application version 20.0. Analysis of research data was used path analysis. This study found that work culture have direct and indirect effects on job satisfaction of employee in Health Office of Pariaman City.